Phenotypic diversity for agro-morphological traits in pigeon pea landraces [(Cajanus cajan L.) Millsp.] cultivated in southern Benin - ADOUKONOU-SAGBADJA, Hubert (My University, 2019)
Pigeon pea is an important but unfortunately neglected grain legume crop in Benin. In this study, the phenotypic diversity in 84 landraces from Benin and four advanced varieties were evaluated at two locations during two consecutive rainy seasons. Twelve quantitative and ten qualitative variables were recorded. A wide range of variation was observed in qualitative traits as well as in quantitative variables. The overall Shannon– Weaver diversity index ranged from 0.41 (pod hairiness) to 1.51 (seed colour). Analysis of variance revealed highly significant differences among accessions for all quantitative traits, except the number of seeds per pod, the days to maturity and the seed yield per plant. In all quantitative traits, phenotypic coefficient of variation was higher than genotypic coefficient of variation indicating a substantial environmental effect on their variability. However, some traits (days to flowering, pod width, number of secondary branches and 100 seed weight) showed great value of heritability. Hierarchical clustering on principal components subdivided the collection from Benin into two groups that were clearly separated from the group of advanced varieties. The results gathered from this study have important implications for pigeon pea germplasm characterization and conservation while the inferred phenotypic groups could be used for parental selection and heterotic crossings in pigeon pea breeding in Benin.
Keywords: Benin; Cajanus cajan; Heritability; Phenotypic; diversity; agro-morphological traits